2019
DOI: 10.2147/dmso.s195456
|View full text |Cite
|
Sign up to set email alerts
|

<p>Quercetin improves lipid metabolism via SCAP-SREBP2-LDLr signaling pathway in early stage diabetic nephropathy</p>

Abstract: Purpose: Quercetin, the most widely distributed flavonoid, has been shown to have multiple properties and beneficial effects on various metabolic diseases. Thus, our aim was to investigate the underlying mechanism whereby quercetin regulates renal lipid accumulation and ameliorates early diabetic renal injuries in Lepr db /Lepr db (db/db) mice, a model of type 2 diabetes. Methods: db/db mice were administered either 50 mg/kg or 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 51 publications
5
32
0
Order By: Relevance
“…Recently, a study performed by Jayachandran et al demonstrated the capacity of isoquecertin to regulate lipid metabolism via AMPK pathway [196]. Besides, quercetin was also able to reduce lipid accumulation in the kidney, individually or in association with allopurinol, a uric acid inhibitor [197,198]. Resveratrol and anthocyanin-rich Seoritae extract prevents lipotoxic and glucotoxic effects through AMPK-PGC-1α axis in db/db mice [199,200].…”
Section: Polyphenols Flavonoids and Nutraceuticalsmentioning
confidence: 99%
“…Recently, a study performed by Jayachandran et al demonstrated the capacity of isoquecertin to regulate lipid metabolism via AMPK pathway [196]. Besides, quercetin was also able to reduce lipid accumulation in the kidney, individually or in association with allopurinol, a uric acid inhibitor [197,198]. Resveratrol and anthocyanin-rich Seoritae extract prevents lipotoxic and glucotoxic effects through AMPK-PGC-1α axis in db/db mice [199,200].…”
Section: Polyphenols Flavonoids and Nutraceuticalsmentioning
confidence: 99%
“…Quercetin belongs to the avonol group of polyphenolic compounds, which functions as antibacterial, antiviral, anti-in ammatory, antioxidant, anticancer, anti-diabetic, immunomodulatory, etc [72]. The existing studies [73][74][75]have provided convincing evidence on the renoprotective effects of quercetin in both animal and cell models of DKD. In addition to its antiviral, anti-in ammatory, antioxidant, anti-cancer and anti-diabetic properties, Ellagic acid also exerts hepatoprotective effect [76].…”
Section: Discussionmentioning
confidence: 99%
“…They found that five flavonoids from Abelmoschus manihot at 5 μmol L −1 could accelerate preadipocytes proliferation and regulate the expression of PPARγ, C/EBPα, SREBP-1, adiponectin, resistin, and visfatin in 3T3-L1 adipocyte, which implicating that Abelmoschus manihot has effects in increasing glucose utilization and improving insulin resistance (Cai et al, 2017 2017Improve lipid metabolic disorders by activating PPARα/γ and attenuating ER stress SD rats Ge, Miao, Sun, and Yu (2016) Down-regulating the activation of p38MAPK and/or Akt pathways as well as the expressions of TGF-β1 and/or TNF-α STZ-induced rats Mao et al (2015) Reduce the expression of TGF-β1 and improve the infiltration and activation of inflammatory cells in glomeruli by intervening p38MAPK signaling SD rats Zhao et al (2012) Attenuate Fibronectin and Collagen IV accumulation in renal glomerulus via miR-21/MMP-9 axis db/db mice Zhang et al (2016) Inhibit glomerular basement membrane damage by inhibiting podocyte heparanase expression STZ-induced C57BL6 mice Podocyte An et al (2011) Improve lipid metabolism via SCAP-SREBP2-LDLr signaling pathway in early stage of DKD db/db mice Jiang, Yu, Wang, Ge, and Li (2019) Abbreviations: ADRN, adriamycin-induced nephropathy; AKI, acute kidney injury; CKD, chronic kidney disease; CRF, chronic renal failure; DKD, diabetic kidney disease; ER, endoplasmic reticulum; HK-2, human renal tubular epithelial cells; IgAN, IgA nephropathy; IR, ischemia/reperfusion; OMA1, OMA1 zinc metallopeptidase; OPA1, optic atrophy 1; SD, Sprague-Dawley; STZ, streptozotocin.…”
Section: Huangkui Capsule and Its Chemical Constituents Pharmacokimentioning
confidence: 99%
“…The accumulation of lipids, lipotoxicity and lipid metabolism dysregulation are associated with renal injury(An et al 2017). Jiang et al have investigated that quercetin improved lipid metabolism via SCAP-SREBP2-LDLr signaling pathway in early stage DKD of db/db mice(Jiang et al, 2019).Taking together, the data from experiments with animal models and cell cultures as described above have implicated that the possible mechanisms of Huangkui capsule treatment in kidney diseases may include reducing inflammation, improvingimmune response, anti-oxidative stress, protecting renal tubular epithelial cells, inhibiting renal fibrosis, regulating autophagy and mitochondrial dynamics. A schematic diagram implicating the possible molecular mechanisms of Huangkui capsule for treatment of kidney diseases is represented in Figure 2.…”
mentioning
confidence: 99%